Conceptualizing non users of the internet and mapping digital (dis)engagement - Park, Sora; Middleton, Catherine; Allen, Matthew; Freeman, Julie; Rickard, Scott; Nansen, Bjorn; Arnold, Michael; Wilken, Rowan; Gibbs, Martin; Williams, Jocelyn (AoIR Selected Papers of Internet Research, 2013)
Very high speed national broadband networks are being rolled out across Australia and New Zealand. Driven by the national governments, Australia’s National Broadband Network (NBN) and New Zealand’s Ultra-Fast Broadband Initiative (UFB) will reshape telecommunications infrastructure with the expectation that ubiquitous connectivity will bring value to all. By highlighting perennial issues of digital engagement and inclusion, this panel questions whether enabling ubiquitous connectivity is sufficient to bring widespread benefit across society. Drawing from a conceptual framework that problematizes and redefines the concept of non-users of the internet, the five papers presented foreground concerns surrounding digital engagement by highlighting mechanisms of resistance. A variety of empirical methodological approaches are used to examine opportunities and challenges for less engaged users in Australia and New Zealand. The papers offer a range of perspectives on digital disengagement within the context of the public’s everyday internet use. Together, these papers provide broad insight into the appropriation of digital technologies, and responses from both the public sector and communities towards fostering digital engagement. Rather than assuming that the provision of information and communication technology (ICT) will render effective uses, emphasis is placed on the ways that users and organizations resist new technologies and the context in which such resistance unfolds. The first paper, “Conceptualizing the non and low users of the internet”, provides a broad framework to investigate digital engagement and offers context for the specific case studies presented by other panelists. While there have been studies that examine different uses of the internet, less attention has been given to the varied degrees of non or low level uses. Acknowledging that there is a considerable variation among non-users, the paper examines a broader spectrum of non to low Internet uses and conceptualizes these in terms of digital disengagement. Second, “Users and non-users of next generation broadband” presents a case study of household broadband adoption and non-adoption in Brunswick, Victoria in Australia, which is one of the early release sites of the Australian NBN. The paper identifies that adoption of broadband does not occur in isolation, but as part of an increasingly dense household media ecology of digital infrastructures, devices, services and knowledge. The third paper, “Mum. Dad. Do you need some help with that? Empowering older Australian adults in a digital era”, examines the challenges middle and older aged people experience while adapting to the digital technologies used to communicate with family members. It explores limitations in digital media literacy, particularly surrounding understandings of devices, forms of connectivity, and installation of devices, and highlights how digital connectivity may cause intergenerational tensions. Fourth, “Authentic representation in the digital opportunity context” explores community engagement schemes that are designed to overcome digital inequality by way of providing infrastructure development, services, and ongoing social and technical support at a local level. Such schemes empower those who would otherwise not have access to digital technologies by facilitating authentic storytelling and representing people’s experiences using their own ’voice’. The paper critically evaluates the relative authenticity of two approaches to social media voice and participation in the context of community engagement. The final paper, “Digitally disengaged: Government resistance to civic participation”, examines digital engagement through an Australian local government study conducted in the City of Casey, Victoria. It highlights government non-use of official spaces for civic participation, and suggests that current limitations to online involvement are often the result of insufficient government reception of, and responses to, citizens’ views. The papers presented in this panel illustrate that improved access to technological infrastructure will not routinely transfer into effective use of ICTs and increased digital engagement for all, as often implicitly assumed by governments. These empirical investigations of individual users, households, communities, and organizations highlight a complex interplay between ICT infrastructure, acceptance and adoption of digital media. Individual and institutional variables and settings hold considerable roles in shaping capacity to access, literacy to use, and the effectiveness of communication through digital technologies. As such, this panel illustrates that digital engagement is influenced by the capabilities and willingness of individuals, communities and organizations to decipher, adapt to, and identify potential benefits from digital media use. This observation should be reflected in government policies and practices intended to encourage digital inclusion. The identified issues associated with non and low Internet use indicate, however, that while digital engagement can and will be fostered, various forms of resistance towards technology use in everyday practice are also likely to persist.